SIMULASI PELIMPAHAN BEBAN SISTEM PMT KOPEL TO KOPEL PADA SAAT PEMELIHARAAN TRAFO BERBASIS ARDUINO MEGA 2560 MENGGUNAKAN VT SCADA 11.2 - Samputro, Muhammad Rizki; Subari, Arkhan (Vocational School Diponegoro University, 2019)
Mochammad Rizki Samputro, Arkhan Subari in this paper explains that the need for electricity in everyday life demands PT. PLN to always maintain the distribution of electrical energy to customers. Therefore, it is necessary to use a strategy to prevent blackouts if the transformer is being maintained, that is by maneuvering the load through the network or by using a 20 KV coupling system. The 20 KV Coupling System consists of PMT Kopel Transformer 1 and PMT Kopel Transformer 2 or often called PMT Kopel to Kopel. In this research, a Kopel to Kopel PMT simulation tool is used to transfer transformer loads during maintenance using a LY2N DPDT 12 V relay, ZMCT103C current transformer sensor, voltage sensor, tap changer and use Arduino Mega 2560 as a delivery choice change. After the experiment, the total current size of transformer 1 and transformer 2 exceeds the capacity of transformer which is 4.29 A and the voltage difference is 0.71 V (5.9 %). Therefore it is necessary to adjust the current and voltage regulation so that it becomes 2.82 A and 0.06 V (0.5 %). After that the transfer of load Transformer 2 to Transformer 1 using PMT Kopel to Kopel can be done. The load transfer is done by entering the PMT Kopel 1 and PMT Kopel 2 simultaneously and the Incoming 2 PMT is released. For the normalization, PMT Incoming 2 is entered and PMT Kopel 1 and Kopel 2 are released simultaneously.